(untitled) (Scientific journal of the Fergana State University, 2024)
The article talks about the influence of Yusuf’s story, reflected in examples of world, in particular, Uzbek oral and written literature, general aspects in matters of image, idea and artistry. The gradual processes of Yusuf’s ascent from a mythological hero to a mature artistic image are analyzed.